Effect of landslope on uniformity of water distribution of sprinklers - JIGIMON T; Dr. Jobi V. Paul (Guide) (Tavanur 1996 Kelappaji College of Agricultural Engineering and Technology)
Effect of landslope on uniformity of water distribution of sprinklers
Effect of landslope on uniformity of water distribution of sprinklers